Sviluppo, implementazione e valutazione funzionale di un nuovo modello protesico di caviglia - Romagnoli, Matteo <1975> (Alma Mater Studiorum - Università di Bologna, 2009)
Total ankle arthroplasty (TAA) is still not as satisfactory as total hip and total knee arthroplasty. For the TAA to be considered a valuable alternative to ankle arthrodesis, an effective range of ankle mobility must be recovered. The disappointing clinical results of the current generation of TAA are mostly related to poor understanding of the structures guiding ankle joint mobility. A new design (BOX Ankle) has been developed, uniquely able to restore physiologic ankle mobility and a natural relationship between the implanted components and the retained ligaments. For the first time the shapes of the tibial and talar components in the sagittal plane were designed to be compatible with the demonstrated ligament isometric rotation. This resulted in an unique motion at the replaced ankle where natural sliding as well as rolling motion occurs while at the same time full conformity is maintained between the three components throughout the flexion arc. According to prior research, the design features a spherical convex tibial component, a talar component with radius of curvature in the sagittal plane longer than that of the natural talus, and a fully conforming meniscal component. After computer-based modelling and preliminary observations in several trial implantation in specimens, 126 patients were implanted in the period July 2003 – December 2008. 75 patients with at least 6 months follow-up are here reported. Mean age was 62,6 years (range 22 – 80), mean follow-up 20,2 months. The AOFAS clinical score systems were used to assess patient outcome. Radiographs at maximal dorsiflexion and maximal plantar flexion confirmed the meniscalbearing component moves anteriorly during dorsiflexion and posteriorly during plantarflexion. Frontal and lateral radiographs in the patients, show good alignment of the components, and no signs of radiolucency or loosening. The mean AOFAS score was observed to go from 41 pre-op to 74,6 at 6 month follow-up, with further improvement at the following follow-up. These early results reveal satisfactory clinical scores, with good recovery of range of motion and reduction of pain. Radiographic assessment reveals good osteointegration. All these preliminary results confirm biomechanical studies and the validity of this novel ligamentcompatible prosthesis design. Surely it will be important to re-evaluate these patients later.